Tumor-Penetrating Delivery of siRNA against TNFα to Human Vestibular Schwannomas. Issue 1 (December 2017) - Ren, Yin; Sagers, Jessica; Landegger, Lukas; Bhatia, Sangeeta; Stankovic, Konstantina
Abstract Vestibular schwannoma (VS) is the most common tumor of the cerebellopontine angle, and it typically presents with sensorineural hearing loss. The genomic landscape of schwannoma is complex and many of the molecules implicated in VS pathogenesis represent targets not amenable to antibody-based or small molecule therapeutics. Tumor-targeted delivery of small interfering RNA (siRNA) therapeutics provides a direct and effective means to interrogate targets while minimizing off-target effects. To establish a preclinical model for therapeutic inhibition of putative targets in VS, archived tumor specimens, fresh tumor cells derived from patients with sporadic VS, and an established schwannoma cell line were screened. Nanoparticles directed by the tumor-homing peptide iRGD were selectively taken up by primary VS culturesin vitro via interactions with αvβ3/β5 integrins and neuropilin-1 (NRP-1). Cellular uptake was inhibited by a neutralizing antibody against αv integrin in a dose-dependent manner. When applied to primary VS cultures, iRGD-targeted nanoparticles delivered siRNA directed against TNFα in a receptor-specific fashion to potently silence gene expression and protein secretion. Taken together, our results provide a proof of principle for tumor-targeted, nanoparticle-mediated delivery of siRNA to VS and establish a novel platform for the development and pre-clinical screening of molecular therapeutics against VS.